ANALISIS REALISASI PENERIMAAN PAJAK PADA KPP PRATAMA MAKASSAR UTARA - Aulia, Fira Andhara; Burhan , Imron; Ka, Veronika Sari Den (PT Bone Jaya Kreatif, 2023)
This study aims to determine the realization of the achievement of tax revenue targets at the North Makassar Tax Office, to find out the efforts of the North Makassar Tax Office to achieve the realization of tax revenues in 2021 from the predetermined targets and the factors that influence the realization of tax revenues at the North Makassar Tax Office in 2021 in achieving predetermined targets. The results of the study indicate that the realization of tax revenues at the North Makassar Tax Office in 2021 has increased. Efforts to realize tax revenue at the North Makassar Tax Office are conducting tax extensification activities, tax intensification, socialization with government agencies and private institutions as well as conducting tax collection and audit activities. Factors that affect the increase in the realization of tax revenues at the North Makassar Tax Office are external factors in the form of economic growth whose fluctuations increase in line with tax revenues and taxpayer compliance in paying taxes and internal factors, namely the DSE application (Target List Extensification), APPROWEB (Website-Based Profile Application), increased tax compliance audits and socialization to government and private agencies. Increasing the amount of tax revenue can achieve the target by improving the performance of tax officials.